The carpenter eaudiobook A story about the greatest success strategies of all. - Gordon, Jon (Your Coach Digital, 2014)
Bestselling author Jon Gordon returns with his most inspiring book yet—filled with powerful lessons and the greatest success strategies of all. Michael wakes up in the hospital with a bandage on his head and fear in his heart. The stress of building a growing business, with his wife Sarah, caused him to collapse while on a morning jog. When Michael finds out the man who saved his life is a Carpenter he visits him and quickly learns that he is more than just a Carpenter; he is also a builder of lives, careers, people, and teams. As the Carpenter shares his wisdom, Michael attempts to save his business in the face of adversity, rejection, fear, and failure. Along the way he learns that there's no such thing as an overnight success but there are timeless principles to help you stand out, excel, and make an impact on people and the world. Drawing upon his work with countless leaders, sales people, professional and college sports teams, non-profit organizations and schools, Jon Gordon shares an entertaining and enlightening story that will inspire you to build a better life, career, and team with the greatest success strategies of all. If you are ready to create your masterpiece, read The Carpenter and begin the building process today.